The effect of learning strategies on offloading decisions in response recall. - Donet, Jenna R.; Marshall, Philip H.; Serra, Michael J. (Memory & Cognition, 2026)
The decision-making processes involved in relying on an external source (cognitive offloading) for memory retrieval tasks have been discussed in numerous publications. The nature of original learning strategies could be an important contributing factor to the decision to offload but is unexamined. In this study we used a paired-associate learning task to investigate the influences of mnemonic (associative) and rote learning strategies on the likelihood of opting out, either by offloading or omitting a response. Further, we investigated the ways that certain outcome variables (specifically, the number of opt-out responses and amount of time spent studying) may in fact influence the relationship between learning strategy and decisions to persist in effortful search. We also investigated the degree to which any effects of learning strategy are specific to either offloading or omission decisions. Overall, we found a mnemonic learning effect of decreased frequency of general opt-out decisions relative to the rote group. Further, we found that mnemonic learning led to longer internal search times prior to opt-out responses, suggesting additional, intentional search processes such as trying to retrieve the original mnemonic, to help recover the response word. A partial mediation of the learning strategy effect on omission latency by performance factors suggested the learning strategy effect affects omission latency independently. Finally, relative to the rote learning strategy, the mnemonic strategy led to fewer instances of offloading, and longer decision latencies for omission responses.